KDM1A Promotes Immunosuppression in Hepatocellular Carcinoma by Regulating PD-L1 through Demethylating MEF2D - Yonglan Wang; Kun Cao (Journal of Immunology Research)
Background. Immune checkpoint inhibitor therapy targeting antiprogrammed cell death-1 (anti-PD-1) or its ligand (anti-PD-L1) is effective in the treatment of some hepatocellular carcinomas (HCC). Hence, further identification of biological targets related to PD-L1 regulation in HCC is beneficial to improve the clinical efficacy of immunotherapy. Some HCC cells express lysine-specific demethylase 1A (KDM1A), which is implicated in the reduced survival time of patients. Here, we studied whether the level of PD-L1 and the immunosuppression are regulated by KDM1A and its miRNA in HCC cells. Methods. In the present study, we studied clinical data from The Cancer Genome Atlas (TCGA) database. We performed qPCR and western blotting assays to measure the expression level of genes of interest. PD-L1 expression was also analyzed by FACS. Clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 was used to generate gene knockout cells to investigate the relationships of genes of interest. We also developed a reporter gene assay (RGA) to explore the changes in T cell-induced antitumor immunity relative to PD-L1 expression in HCC cells. The binding between proteins and promoters or miRNAs and their target genes was explored by luciferase reporter assays. Results. The results showed that PD-L1 and KDM1A were increased in HCC patients and cells, and KDM1A promoted the expression of PD-L1 in HCC cells. Our findings showed that the enhancement of PD-L1 expression was not attributed to mitochondrial dysfunction caused by increases in KDM1A in HCC cells. Furthermore, we observed a lower level of MEF2D methylation in HCC cells than in normal human liver cells. Demethylated MEF2D could bind to the promoter of PD-L1 and activate its expression, while KDM1A interacted with MEF2D and acted as a demethylase to reduce its methylation. Moreover, a new miRNA, miR-329-3p, targeting KDM1A was found to regulate the PD-L1 expression profile in HCC cells. In the xenograft model, the tumors treated with miR-329-3p showed growth inhibition. Conclusions. Mechanistically, miR-329-3p inhibits tumor cellular immunosuppression and reinforces the response of tumor cells to T cell-induced cytotoxic effect by targeting KDM1A mRNA and downregulating its expression, which contributed to MEF2D demethylation and activation of PD-L1 expression.